An international, randomized, placebo‐controlled, phase 2b clinical trial of intepirdine for dementia with Lewy bodies (HEADWAY‐DLB). Issue 1 (20th June 2021) - Lang, Frederick M.; Kwon, Daniel Y.; Aarsland, Dag; Boeve, Brad; Tousi, Babak; Harnett, Mark; Mo, Yi; Noel Sabbagh, Marwan
Abstract: Introduction: A phase 2b clinical trial, HEADWAY‐DLB, was performed to assess treatment with intepirdine, a serotonin receptor antagonist, in patients with dementia with Lewy bodies (DLB). Methods: HEADWAY‐DLB was a multinational, double‐blind, randomized, placebo‐controlled study. Two hundred sixty‐nine DLB patients were randomized to receive placebo, 70 mg/day intepirdine, or 35 mg/day intepirdine over 24 weeks. The primary endpoint was change from baseline to week 24 on the Unified Parkinson's Disease Rating Scale–Part III (UPDRS‐III). Results: Both intepirdine groups did not demonstrate significant benefits over placebo at 24 weeks on the UPDRS‐III (35 mg/day: P  = .1580, 70 mg/day: P  = .6069). All other endpoints were not significant. Intepirdine was well tolerated, with a slightly higher incidence of gastrointestinal adverse events observed in the intepirdine groups versus placebo. Discussion: Intepirdine treatment did not lead to improvements over placebo in patients with DLB. As one of the largest DLB studies to date, HEADWAY‐DLB demonstrates that international trials for DLB are feasible within a reasonable timeframe.